Traditional and interactive display methods: do they increase sensorial shopping experience and purchase intention for luxury e-commerce? - Marques, Paula Bernardo da Silva (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence